2000
DOI: 10.1055/s-2000-8501
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Pediatric Heart, Heart-Lung, and Lung Transplant Recipients

Abstract: Few studies have assessed quality of life in pediatric heart and/or lung transplant recipients, and have varied by the tool used, the design employed, and the time of assessment from transplant. The results also varied including normal to abnormal "psychologic adjustment", diminishing problem behavior at home following transplantation, as well as improvements and no change in quality of life using tools designed specifically for the objective assessment of quality of life. This area of study is in its infancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Unfortunately, we did not collect information on pre-transplant diagnosis that might affect a child's perceptions after transplant, although the relevance of this variable is unclear because conflicting findings have been reported. 2,5,18,25 There was no pre-transplant assessment, and children were only assessed once at varied intervals after transplant. Other studies have shown improvement in physical and psychosocial functioning after transplant compared with before transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we did not collect information on pre-transplant diagnosis that might affect a child's perceptions after transplant, although the relevance of this variable is unclear because conflicting findings have been reported. 2,5,18,25 There was no pre-transplant assessment, and children were only assessed once at varied intervals after transplant. Other studies have shown improvement in physical and psychosocial functioning after transplant compared with before transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Agreement between parents and children in our study on ratings of child QoL were limited as demonstrated by the large absolute difference in total scores (Table ), reinforcing the importance of self‐reported outcomes . Differences between self‐ and parent‐reported raw scores were smaller post‐LTx for all domains aside from emotional functioning, compared to pre‐LTx raw scores.…”
Section: Discussionmentioning
confidence: 63%
“…Multi‐site investigations are required to provide larger, more diverse samples, which would help to achieve sufficient statistical power and more generalizability of findings. Research is also necessary to explore methods for standardized integration of validated QoL measurement tools into clinical practice . These research initiatives would result in critical insights for healthcare professionals working in the field of pediatric LTx and may lead to improved QoL outcomes for this vulnerable population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indications for pediatric LTx are different from adults, and measures of childhood development must be included in the assessment of QoL in children. To date, published research investigating QoL in pediatric lung transplant recipients has largely been descriptive and contains limitations regarding study design and methodology (31). Nonetheless, in a recent study, 80% of children surviving seven yr after LTx had no activity limitation (32), overall health‐related QoL in children and adolescents was found to be vastly improved following LTx, and the majority of pediatric recipients had normal development and cognitive function.…”
Section: Suggesting a Path Forwardmentioning
confidence: 99%